Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1439-037x.2009.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Absorption of K over Na in Sugar Beet Cultivars and its Relationship with Yield and Quality in Two Contrasting Environments of Central Greece

Abstract: Selective absorption (SA) of K over Na (i.e. the preferential absorption of K over Na) has been proposed as a Na tolerance mechanism but genotypic variation for this trait has not been assessed with sugar beet in the field. Thus, the aim of this study was to explore the variation of SA in 14 sugar beet cultivars and to relate SA with yield and root quality in two sites of central Greece (Amfithea and Pyrgetos). Genotypic variation for SA was significant and the SA values were higher in Pyrgetos, the site with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…Exclusion of Na in favour of K was beneficial for SY up to a K/Na ratio value of 5.74. Yet, higher ratios negated this impact on yield in accordance with findings in the semi‐halophytic sugar beet (Tsialtas and Maslaris ). Given the ability of Ca 2+ to block Na + ‐permeable (non‐selective) NSCC channels (Demidchik and Tester ), higher leaf Ca 2+ may be also beneficial for retaining more Na + in leaves, to be used for osmotic purposes.…”
Section: Discussionsupporting
confidence: 86%
“…Exclusion of Na in favour of K was beneficial for SY up to a K/Na ratio value of 5.74. Yet, higher ratios negated this impact on yield in accordance with findings in the semi‐halophytic sugar beet (Tsialtas and Maslaris ). Given the ability of Ca 2+ to block Na + ‐permeable (non‐selective) NSCC channels (Demidchik and Tester ), higher leaf Ca 2+ may be also beneficial for retaining more Na + in leaves, to be used for osmotic purposes.…”
Section: Discussionsupporting
confidence: 86%
“…However, in most cases, altering only one of the impurity components resulted in only small changes in the traits normally associated with the economic value of the crop, i.e., root yield, sucrose concentration, loss-to-molasses, and recoverable sucrose per ton. Environment (years in this study) also can have a large impact on the concentration of some variables and change relationships among the components, as was observed with the potassium:sodium ratio and its relationship with sucrose, amino-nitrogen, and dry matter concentration (Tsialtas and Maslaris, 2009). A four-year trial with the pollinator lines used in this study provides further evidence that environment influences associations among impurity components and their relationships to processing quality.…”
Section: Discussionsupporting
confidence: 62%
“…Carter (1986) observed that an increase in the sodium concentration, or a decrease in the potassium:sodium ratio, decreased dry matter concentration and reduced sucrose concentration. Tsialtas and Maslaris (2009) concluded that cultivars that limit potassium uptake while favoring sodium absorption had lower sucrose concentrations due to the dilution of sucrose caused by a decrease in dry matter concentration. The correlation between the ability of a cultivar to limit sodium in the root and amino-nitrogen concentration was positive.…”
Section: Discussionmentioning
confidence: 99%
“…Those results might be explained by dilution of sucrose due to the increased water content in storage roots (Tsialtas and Maslaris 2009). The content of melassogenic substances such as K and Na in storage roots were significantly modified by interaction between K-Mg-Na ratios and locations (F 12,180 = 1.97; P < 0.05 and F 12,180 = 6.24; P < 0.001).…”
Section: Resultsmentioning
confidence: 96%